The Interplay of Information Literacy, Learning Facility, Learning Achievement & Motivation Toward Online Learning Experience During COVID-19 Crisis: PLS-SEM Approach - Prihandoko, Lastika Ary (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The COVID-19 crisis has forced the learning system in Indonesia from face-to-face learning to online learning. This rapid transformation presents various challenges, especially for universities in remote areas such as Papua. This study aims to explore the factors that can influence the students' learning experience. The research approach used is quantitative with an analysis model of PLS-SEM. The data were obtained using a simple random sampling technique from four universities in Merauke, with 207 respondents. Four hypotheses were accepted, and one hypothesis was rejected in this research. Online information literacy experience and online learning facility perspective were affecting online learning experience significantly. Meanwhile, the online learning facility perspective significantly affecting online information literacy experience and online learning achievement motivation. However, online learning achievement motivation has a positive correlation but does not contribute significantly to an online learning experience. This research implies that higher education institutions can focus on factors that significantly contribute to the student's learning experience to provide a positive experience and increase online learning effectiveness, especially during the COVID-19 crisis.Keywords: learning experience, online learning, PLS-SEM, COVID-19